An investigation of differences in attitudes and values between freshmen and sophomores at the University of the Philippines, Diliman - De Boer, Stewart Westerhof 1928-
The purpose of this study was to determine the differences in attitudes, values and perceptions of the campus environment between freshmen and sophomores of the University of the Philippines, Diliman if there is any, and relate the differences to gender or socio-economic subgroupings of students. The subjects consisted of 418 students. The Allport-Vernon-Lindzey Study of Values was chosen for the measurement of attitudes and values and the College and University Environment Scales (CUES) to measure perception of the campus environment. Other methodological studies that would look into yearly changes in perceptions are needed.